Immunohistochemistry as a Detection Tool for Ion Channels Involved in Dental Pain Signaling - Rosmaliza Ramli; Siti Norasikin Mohd Nafi; Nurulezah Hasbullah; Nurhafizah Ghani; Nor Azura Ahmad Tarmidzi (Elsevier, 2024)
Indexed by WOS/ Scopus